P035 Clostridium difficile infection in ulcerative colitis: Data from the tofacitinib clinical program and an insurance claims database. (July 2019) - Edward, Loftus; Alessandro, Armuzzi; Daniel, Baumgart; Marco, DiBonaventura; Jeffrey, Curtis; Gary, Chan; Eric, Maller; Daniel, Quirk; Haiyun, Fan; Nana, Koram; Leonardo, Salese; Chinyu, Su
Abstract : BACKGROUND: Patients with inflammatory bowel disease (IBD), particularly ulcerative colitis (UC), have a higher risk of Clostridium difficile infection (CDI) than the general population (1 ). The incidence of CDI is increasing among patients with IBD, and certain UC treatments may be associated with greater risk (1 ). We report CDI events in the tofacitinib UC clinical program, and the incidence of CDI among patients receiving other treatments for UC. METHODS: For the tofacitinib UC program, rates of CDI (patients with an adverse event [AE] of CDI, Clostridium difficile colitis, or Clostridium test-positive, plus concomitant oral metronidazole or vancomycin, counted once per cohort) are reported for Induction Cohort (patients from an 8-week Phase [P]2 and two 8-week P3 induction studies; placebo or tofacitinib 10 mg twice daily [BID; NCT00787202; NCT01465763; NCT01458951]); Maintenance Cohort (patients from a 52-week maintenance study; placebo or tofacitinib 5 or 10 mg BID [NCT01458574]); and Overall Cohort (all tofacitinib-treated patients in P2/3 induction and maintenance studies and an ongoing, open-label, long-term extension study [as of December 2016; NCT01470612]). Positive Clostridium difficile test at screening was an exclusion criterion for program entry. Overall Cohort incidence rate (IR) was calculated as number of unique patients with events per 100 patient-years (PY). For contextualization, CDI rates among patients receiving other UC medications were obtained from a retrospective cohort study utilizing data from the Truven MarketScan ® Database, an administrative healthcare claims database in the US. Patients with moderately to severely active UC, with either an inpatient or outpatient diagnosis code of CDI, plus a prescription for oral therapy (including metronidazole, vancomycin, and fidaxomicin) within 14 days of CDI diagnosis (observation period: October 1, 2010–September 30, 2015), were included. Truven cohort IRs were calculated as number of patients with events per 100 PY. RESULTS: In the tofacitinib Induction Cohort, CDI occurred in 3 patients (placebo, 1/282 [0.4%]; tofacitinib 10 mg BID, 2/938 [0.2%]). In the Maintenance Cohort, CDI occurred in 3 patients (placebo, 3/198 [1.5%]; tofacitinib 5 or 10 mg BID, 0/394 [0.0%]). In the Overall Cohort of all tofacitinib-treated patients (1, 664 PY of follow-up), CDI occurred in 8/1, 157 patients (0.7%), with an IR (95% confidence interval [CI]) of 0.48 (0.21, 0.95). Two cases were reported as serious AEs. All were mild (n = 4) or moderate (n = 4) in severity; 6 continued with study treatment, one temporarily discontinued, one permanently discontinued. All CDI cases resolved with treatment. In the Truven Cohort, 160 CDI events occurred during 4, 918 PY of follow-up, with an overall CDI IR (95% CI) of 3.25 (2.77, 3.80); of which 116 were CDI-associated hospitalizations (4, 936 PY of follow-up). Among patients receiving azathioprine, 6-mercaptopurine, or tumor necrosis factor inhibitors, CDI IRs were 3.23 (2.18, 4.62), 2.31 (1.26, 3.87), and 3.58 (2.95, 4.29), respectively. CONCLUSION(S): In the tofacitinib UC program, CDI rates among patients receiving tofacitinib were similar to or lower than those observed with placebo. The IR among patients receiving tofacitinib was numerically lower than those observed for immunomodulators and tumor necrosis factor inhibitors in the Truven Cohort.